Ante- and post-natal knowledge of breastfeeding and its practice within six weeks of postpartum period among mothers in a public hospital, Selangor, Malaysia - Ibrahim, Nurul Hidayu (2020)
Introduction: Breastfeeding (BF) is the normal way of feeding a newborn. Exclusive breastfeeding (EBF) is defined as providing breast milk to the infant. It is known as the feeding option with the most advantages for infants. Even though the benefits of EBF towards mothers and infants are well-established, the rate of EBF is still not encouraging. To promote and sustain EBF practices, the Breastfeeding Hospital Initiatives (BFHI) was launched by World Health Organization (WHO) and United Nation Children Emergency Funds (UNICEF) in 1991. Malaysia has been accredited as the third country in the world that successfully practises BFHI in almost all the government hospitals. One crucial step in the implementation of BFHI is to provide all the antenatal mothers with sufficient breastfeeding knowledge to enable them to practise EBF. Objective: The aim of this study is to study the antenatal knowledge on breastfeeding and its practice within six week of postpartum period among mothers in antenatal clinic in a public hospital, Selangor. Method: A total of 348 antenatal mothers were recruited in a cross-sectional study conducted in an antenatal clinic of a public hospital in Malaysia. Knowledge on breastfeeding was identified using pre- and post-test questionnaires. In each questionnaire, the participants answered ten questions related to breastfeeding. In addition, phone calls were made within six weeks to monitor the practice of breastfeeding in the postpartum period. Descriptive analysis was conducted and its association with certain factors were determined using Chi-Square analysis and binary logistic regression analysis. A p-value of less than 0.05 is considered as statistically significant in the study. Result: The percentage of participants that scored good knowledge increased from 79.3% (pre-test) to 81.9% (post-test). Out of 330 participants that being followed-up, 67.6% practice EBF within six weeks of postpartum period and 68.4% of them was having good knowledge on BF. The result also showed that multipara had 1.712 times the odds to practice EBF compare to primipara (p<0.05) and nonworking mothers were 1.778 more likely to EBF compare to working mothers. Furthermore, most mothers were likely to not practising EBF their babies Conclusion: It is important for antenatal mothers to receive information regarding breastfeeding to increase their awareness about its benefits. Informing mother regarding breastfeeding and its management in BFHI plays an important role in educating antenatal mothers on the benefits and management of EBF. The EBF education should also include techniques such as hands-on practical to encourage the successful adoption of EBF for the newborn among working mothers.